Pembuatan Film Pendek “Hidup Mahasiswa Yang Berubah” Dengan Teknik Cinematografi dengan “One-Take” dan Colorgrading - Ahmad Syam, Rhenal; Syafrizal, Agusdi; Zainul Rahman , Muhammad (CV MEDAN TEKNO SOLUSI, 2024)
Film pendek